The Side Effect of Sunscreen in Our Marine - ramandini, putri; nurfitriana, siti (LIAISON JOURNAL OF BEST, 2024)
Sunscreen application is highly important. It can protect our skin from UV exposure and prevent skin cancer. Nowadays, the understanding of people regarding the benefit of sunscreen has been increasing. It shows from the research that sunscreen is the top of skincare habit. Many companies also offer more advantages such as creating combination of sunscreen with whitening or make-up coverage functions. It makes this product achieves raising in sales. Sunscreen is definitely necessary for swimmer. However, some researches tell that the chemicals in the product can be pollutant in our sea. Some materials as oxybenzone and octinoxate in chemical sunscreen can accelerate coral bleaching even killing the coral reef. Meanwhile physical sunscreen, known safer than chemical sunscreen, is actually also contained potentially dangerous materials for marine. The nano particles such as titanium dioxide and zinc oxide recently found that can destruct the coral reef. However, further study is recommended to understand how far the dangerous of physical sunscreen for the sea life. Therefore, the customers are encouraged to seek more information to know which sunscreen that outweighs advantages and consider some more environmental-friendly habit as using UV protection clothes or not swimming during the peak time of sun exposure. Keywords: Chemical Sunscreen, Physical Sunscreen, oxybenzene, octinoxate, titanium dioxide, zinc oxide